Anthraquinone Sulphate Chemical Pulping of Ceiba pentandra - KUMAR WALIA, YOGESH; GUPTA, D.K. (Asian Journal of Chemistry, 2010)
Bleachable grade of pulp is produced by sulphate chemical process because reduced pitch troubles with resinuous wood. The stream pollution and air pollution can be minimised by using anthraquinone. In sulphate pulping, the yield and properties of pulp produced are dependent on two sets of variables, with the fibrous raw material and with the pulping operation. The permagnate number and pulp yield are determined by analysis. On addition of anthraquinone in sulphate process, there is no adverse effect but it is helpful in reducing the cost of pulp.